Bone Marrow CD11c(+) Cell-Derived Amphiregulin Promotes Pulmonary Fibrosis - Ding, Lin (J Immunol, 2016)
Amphiregulin (AREG), an epidermal growth factor receptor ligand, is implicated in tissue repair and fibrosis but its cellular source and role in regeneration vs. fibrosis remain unclear. In this study we hypothesize that AREG induced in bone marrow derived CD11c+ cells is essential for pulmonary fibrosis. Thus the objectives were to evaluate the importance and role of AREG in pulmonary fibrosis, identify the cellular source of AREG induction and analyze its regulation of fibroblast function and activation. The results showed that lung AREG expression was significantly induced in bleomycin-induced pulmonary fibrosis. AREG deficiency in knockout (KO) mice significantly diminished pulmonary fibrosis. Analysis of AREG expression in major lung cell types revealed induction in fibrotic lungs predominantly occurred in CD11c(+) cells. Moreover depletion of bone marrow derived CD11c(+) cells suppressed both induction of lung AREG expression and pulmonary fibrosis. Conversely, adoptive transfer of bone marrow-derived CD11c(+) cells from BLM-treated donor mice exacerbated pulmonary fibrosis but not if the donor cells were made AREG-deficient prior to transfer. CD11c(+) cell conditioned media or co-culture stimulated fibroblast proliferation, activation and myofibroblast differentiation in an AREG dependent manner. Furthermore recombinant AREG induced telomerase reverse transcriptase (TERT) which appeared to be essential for the proliferative effect. Finally AREG significantly enhanced fibroblast motility, which was associated with increased expression of α6 integrin. These findings suggested that induced AREG specifically in recruited bone marrow-derived CD11c(+) cells promoted bleomycin induced pulmonary fibrosis by activation of fibroblast TERT dependent proliferation, motility and indirectly, myofibroblast differentiation.